Implikasi Pendidikan dari Kisah Nabi Musa dan Nabi Khidir dalam Qur’an Surat Al-Kahfi Ayat 69, 70,72,75,78 terhadap Tahapan Pemberian Hukuman - Afifah Fauziah; Ikin Asikin; Dinar Nur Inten (UNISBA Press, 2024)
Abstract. Punishment is an important part of education. Punishment is carried out by educators with the aim of making children aware that the actions they have committed are wrong and should not be repeated. Looking at the current situation and conditions, there are still educators who punish children not according to their portions. Therefore, in an effort to make children aware, of course educators must know the stages of giving punishment, as well as the type of punishment that deters them, but does not cause trauma. This research aims to (1) Find out the opinion of the mufassir about Q.S Al-Kahf verses 69, 70, 72, 75, 78. (2) Find out the essence of Q.S Al-Kahf verses 69, 70, 72, 75, 78 regarding the stages of punishment ( punishment) in the story of the prophet Musa and the prophet Khidir. (3) Find out the opinions of experts regarding punishment. (4) Knowing the educational implications of the story of the prophet Moses and the prophet Khidr contained in Q.S Al-Kahf verses 69, 70, 72, 75, 78 on the stages of administering punishment. The method used in this research is the descriptive-analysis method, the data collection technique is library research, therefore the material object of this research is books/books of interpretation of the Al-Quran, books, articles, journals and other sources which are still available. related to the main research problem. The results of this research show that the stages of administering punishment from the story of the prophet Moses and the prophet Khidr contained in Q.S Al-Kahf verses 69, 70, 72, 75, 78 are: 1) Making agreed rules (learning contracts) as preventive punishment, 2) Giving a warning as the first stage of punishment, 3) Giving a warning as the second stage of giving punishment, 4) Giving punishment (deprivation) as the third stage of giving punishment. Abstrak. Hukuman merupakan bagian penting dalam pendidikan. Hukuman dilakukan oleh para pendidik dengan tujuan untuk menyadarkan anak bahwa perbuatan yang dilakukannya salah dan tidak boleh diulangi. Melihat situasi dan kondisi saat ini masih ada pendidik yang menghukum anak tidak sesuai porsinya. Oleh karena itu, dalam upaya menyadarkan anak, tentunya pendidik harus mengetahui tahapan pemberian hukuman, serta jenis hukuman yang membuatnya jera, namun tidak menimbulkan trauma. Penelitian ini bertujuan untuk (1) Mengetahui pendapat para mufassir tentang Q.S Al-Kahfi ayat 69, 70, 72, 75, 78. (2) Mengetahui esensi Q.S Al-Kahfi ayat 69, 70, 72, 75, 78 tentang tahapan hukuman (punishment) dalam kisah nabi Musa dan nabi Khidir. (3) Mengetahui pendapat para pakar tentang hukuman (punishment). (4) Mengetahui implikasi pendidikan dari kisah nabi Musa dan nabi Khidr yang terdapat dalam Q.S Al-Kahfi ayat 69, 70, 72, 75, 78 terhadap tahapan pemberian hukuman. Metode yang digunakan dalam penelitian ini adalah metode deskriptif-analisis, teknik pengumpulan datanya yaitu kepustakaan (library research) oleh karena itu objek material penelitian ini berupa buku/kitab tafsir Al-Quran, buku, artikel, jurnal, serta sumber-sumber lain yang masih berhubungan dengan pokok masalah penelitian. Hasil penelitian ini menujukkan bahwa tahapan pemberian hukuman dari kisah nabi Musa dan nabi Khidr yang terkandung dalam Q.S Al-Kahfi ayat 69, 70, 72, 75, 78 yaitu : 1) Membuat aturan yang disepakati (kontrak belajar) sebagai hukuman preventif, 2) Memberi teguran sebagai tahap pertama pemberian hukuman, 3) Memberi peringatan sebagai tahap kedua pemberian hukuman, 4) Memberi hukuman (deprivasi) sebagai tahap ketiga pemberian hukuman.